(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Neologisms play a significant role in enriching and modernizing language instruction. In French lessons, their use not only enhances linguistic adaptability but also provides students with an understanding of contemporary cultural and social contexts. This paper explores the pedagogical potential of neologisms in French language teaching, emphasizing their relevance in improving vocabulary acquisition, comprehension, and communication skills. By integrating neologisms into lesson plans, educators can foster a dynamic and engaging learning environment, bridging the gap between traditional curriculum and real-world language use. The study underscores the importance of balancing innovation with foundational language skills to ensure comprehensive linguistic competence among students.